ANALISIS BUDAYA KERJA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KECAMATAN TAJURHALANG KABUPATEN BOGOR - Vanessa Pola Palewa; Udin Saprudin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Work culture plays an essential role in improving employee performance within organizations, including government institutions. This study aims to analyze the work culture in enhancing employee performance at the Tajurhalang District Office, Bogor Regency. The research used a qualitative approach with data collected through observation, interviews, and documentation. The results show that the work culture at the Tajurhalang District Office has not yet been fully optimal. Employee discipline remains low due to insufficient supervision from leaders. Openness among employees is fairly good, although some are still reluctant to express their opinions directly to superiors. Mutual respect among colleagues has been implemented but not consistently. Communication and teamwork need improvement to achieve the desired performance standards. Overall, a strong and positive work culture is expected to encourage sustainable improvement in employee performance.